The voices of physical education teachers: its pressure, measure, and treasure in delivering instruction in physical education - Carla Jobelle Culajara (Indonesian Journal of Research in Physical Education, Sport, and Health, 2023)
The study shed light on addressing the challenges, coping strategies, and instructional approaches of Physical Education teachers. The study employed a qualitative research design using phenomenological, which was participated by 8 PE teachers working as secondary public school teachers in the Philippines. Purposive sampling was used to choose the participants to answer the study's objectives. To determine the results, coding and themes were utilized. There were four emerging themes based on the study's results: challenges in accessibility and availability, students’ interest, continuous personal and professional development, and differentiated teaching approaches. With the new normal of education, there were adjustments in how PE teachers reach the students. As a Physical Education teacher who wants to further their education, being aware of the creative ways that instruction is delivered through the integration of ICT and how technology become a useful tool has developed into a potent tool for interacting with students. This study will help PE teachers understand that, regardless of how challenging it can be to achieve performance tasks, there are various ways to do so. Teachers should work together to continue learning and growing for the students analyzing the study of teaching effectiveness can be analyzed by looking at the measures that physical education teachers use to deliver lessons.